Chapter Lo "studium" e la biblioteca di Santa Maria Novella nel Duecento e nei primi anni del Trecento (con una postilla sul Boezio di Trevet) - Pegoretti, Anna (Reti Medievali E-Book, 2020)
Building on recent scholarship, this article sketches the development of the Florentine studium of Santa Maria Novella in the thirteenth century, before it became a studium generale between 1305 and 1311. The catalogue of Santa Maria Novella's library and the information regarding works which were conceived there are collected and analysed to outline the core of the ancient library. The first quire of the manuscript Florence, Biblioteca Nazionale Centrale, Conv. soppr. G 3.451 (cc. 1-8) constitutes a notable case study for the learning interests of Dominican friars. Finally, this article discusses the controversial letter written by Nicholas Trevet to the dedicatee of his commentary on Boethius' Consolatio Philosophiae and re-assesses its disputed connec- tion with the Florentine environment.